Meningkatkan Nilai Tambah Perusahaan sebagai Implikatif Peran Stakeholder Berprinsip Islami - M. Adi Trisna Wahyudi; Haidar Ali, Mohammad; Ciptanila Yuni K, Kusnul; Nurul Haqq, Zulkifli (Journal of Islamic Management, 2024)
The role of stakeholders is becoming increasingly important in creating added value, especially in the context of Islamic principles which provide an in-depth and holistic view of the concept of corporate value. This research aims to reveal in depth the efforts of PT Pesantren Agrobisnis Agroindustri Mukmin Mandiri in Sidoarjo Regency, an SME owned by an Islamic boarding school, in increasing added value so that it can continue to exist and develop. The research method used is a qualitative case study type, with data collection through direct observation, interviews and document analysis. The research results show that this company has succeeded in increasing added value through product differentiation, further processing, and applying Islamic working principles. These findings contribute to business and management literature, especially for companies that apply Islamic principles, by providing principles for effective and sustainable business strategies.